The impact of agricultural public expenditure on agricultural economic growth : a Sub-Saharan Africa context - Gandiwa-Mudede, Charmaine Sandy (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.